2017
DOI: 10.1016/j.jval.2017.08.479
|View full text |Cite
|
Sign up to set email alerts
|

Health State Utilities in Individuals with Goiter, Hypothyroidism, Hyperthyroidism and Graves’ Disease as an Example for Thyroid Disorders – A Systematic Review

Abstract: A483 (75 patients each). The 75 patients on our intervention group were educated by the Pharmacist on diabetes and hypertension, their complications, risks, preventive measures and management. This was done at least six times during the study period unlike the control group who received no such education. In particular, they were counseled on the need for medication and treatment adherence such as clinic visits, and life style modifications including diet and exercise. Outcome measure included changes in fasti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The mean utility value derived across these 6 health states of patients with active, moderate-severe TED was 0.44. This indicates a substantial level of disutility as compared with the value of 0.88 found in a study investigating QoL in hyperthyroid Graves disease and a chronic, mild TED subgroup . These utility values highlight the substantial impact TED imposes when compared with the US general population (0.85) .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The mean utility value derived across these 6 health states of patients with active, moderate-severe TED was 0.44. This indicates a substantial level of disutility as compared with the value of 0.88 found in a study investigating QoL in hyperthyroid Graves disease and a chronic, mild TED subgroup . These utility values highlight the substantial impact TED imposes when compared with the US general population (0.85) .…”
Section: Discussionsupporting
confidence: 68%
“…This indicates a substantial level of disutility as compared with the value of 0.88 found in a study investigating QoL in hyperthyroid Graves disease and a chronic, mild TED subgroup. 24 These utility values highlight the substantial impact TED imposes when compared with the US general population (0.85). 22 Further, this mean utility value was nearly identical to that calculated with a weighted analysis using proportions of these health states found in 2 controlled trials.…”
Section: Discussionmentioning
confidence: 99%
“…In monetary terms, and based on a population EVSI of £3.64 m per year, the value of a clinical trial would be expected to exceed its cost within 1 year. 36 Literature searches did not identify any health utility measurement 20 or economic evaluations of liothyronine. Judgements on its cost-effectiveness in the UK appear to be made implicitly in policy guidelines, driven in large part by the significant difference in the current unit acquisition cost between liothyronine and levothyroxine.…”
Section: Discussionmentioning
confidence: 99%
“…19 Health utilities Literature searches did not identify any relevant health utility data. 20 Self-selecting people who reported to be clinically unresponsive to levothyroxine alone despite being biochemically euthyroid were recruited to a survey that was advertisement via social media, and hosted on the website of the charity Thyroid UK. Consent was obtained within the online form, following a full explanation of the purpose and nature of the survey.…”
Section: Open Accessmentioning
confidence: 99%
“…Utilities are measured on a cardinal scale between 0 (death) and 1 (full health) reflecting patient preferences for a given state of health. We conducted a comprehensive systematic literature review in PubMed/MEDLINE, Tufts CEA Registry, NHS EED, and Cochrane to identify studies that reported health state utilities for several health states associated with iodine deficiency (34,35). The identified studies report health utility values related to hypothyroidism (n = 7), hyperthyroidism (n = 2), goiter (n = 1), thyroid nodules (n = 11), thyroid cancer (n = 16), and intellectual disability (n = 5).…”
Section: Utilitiesmentioning
confidence: 99%